Konseling Pastoral Dengan Pendekatan Client Centered Kepada Pria Dewasa Penyandang Disabilitas Tuna Daksa Yang Tidak Menerima Dirinya Di Kecamatan Manduamas. - Parapat, Hendra; Rencan C. Marbun; Iwan S. Tarigan (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
Physical impairment is a condition of being damaged or disturbed as a result of deformity or obstacles to the bones, muscles and joints in their normal function. This condition can be caused by disease, accident, or can also be caused by a congenital condition that results in total disability. Physical impairment can also be interpreted as a form of abnormality or disability in the muscle, bone, joint and nervous system caused by disease, viruses and accidents that occur before birth, at birth and after birth. The aim of this research is to find out how adult men with disabilities can accept themselves in Manduamas sub-district. This research uses a qualitative description method. The population of this study was 4 adult men with disabilities. In an effort to provide assistance to adult men with physical impairments, researchers provide assistance with problematic aspects, namely, physical aspects, psychological aspects, social aspects and spiritual aspects. In an effort to provide pastoral counseling assistance using the Cilent Center approach to adult men with disabilities who cannot accept themselves, there are several approaches taken by the assistant, namely, listening, reflecting, explaining, and being fully present. From the research results, pastoral counseling with a client-centered approach can help adult men with disabilities accept themselves.